2019
DOI: 10.1093/pcp/pcz117
|View full text |Cite
|
Sign up to set email alerts
|

FAX2 Mediates Fatty Acid Export from Plastids in Developing Arabidopsis Seeds

Abstract: Vegetable oils are mainly stored in the form of triacylglycerol (TAG) in oilseeds. Fatty acids (FAs), one of the building blocks for TAG assembly, are synthesized in plastids and then exported to the endoplasmic reticulum for storage oil synthesis. A recent study demonstrated that the export of FAs from plastids was mediated by a FAX (FA export) family protein. However, the significance of FAs export from plastid during seed oil accumulation has not been investigated. In this study, we found that FAX2 was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 62 publications
5
25
0
Order By: Relevance
“…This can be partly achieved at the levels post transcription, possibly via protein degradation of excess subunits (Sasaki and Nagano, 2004). β-CT appears to be a quantity control factor -overexpression of β-CT (Madoka et al, 2002), but not BCCP2 (Thelen and Ohlrogge, 2002) or BC (Shintani et al, 1997), could lead to a significant rise in protein levels of all other three subunits, though their mRNA levels were not affected.…”
Section: Key Enzymes and Non-transcriptional Regulationmentioning
confidence: 98%
See 1 more Smart Citation
“…This can be partly achieved at the levels post transcription, possibly via protein degradation of excess subunits (Sasaki and Nagano, 2004). β-CT appears to be a quantity control factor -overexpression of β-CT (Madoka et al, 2002), but not BCCP2 (Thelen and Ohlrogge, 2002) or BC (Shintani et al, 1997), could lead to a significant rise in protein levels of all other three subunits, though their mRNA levels were not affected.…”
Section: Key Enzymes and Non-transcriptional Regulationmentioning
confidence: 98%
“…The novel FAX family consists of seven members. While FAX1 plays a prominent role in leaves and flowers (Li et al, 2015), FAX2 and FAX4 are important for seed oil accumulation (Tian et al, 2019;Li et al, 2020). Of note, FAX1 can rescue yeast (Saccharomyces cerevisiae) mutant defective in FA transport with a cargo preference for 16:0 over 18:1; however, 18:1 is the major FA exported out of plastids (Li et al, 2015).…”
Section: Biosynthesis Of C18 Unsaturated Fatty Acidsmentioning
confidence: 99%
“…FAX1 located in the inner chloroplast membrane acts as an exporter of FAs from the plastid to the cytosol (Li et al ., 2015). Additionally, FAX1 homologue genes might respond to transport FAs out of the chloroplast into the cytosol to form the acyl‐CoA pool (Tian et al ., 2019). GmFAX1 and GmFAX2 were increased on average approximately 10‐fold and 2‐fold, respectively, in nodules compared to roots.…”
Section: Resultsmentioning
confidence: 99%
“…Our data showed that, during legume–rhizobia interactions and the development of nitrogen‐fixing nodules, lipid synthesis and lipid transporter genes were extensively expressed to higher levels in nodules than in roots, from GmFAX1 and its homologues on the plastid envelope (Li et al ., 2015; Tian et al ., 2019) to GmABCA1 on the ER membrane (Kim et al ., 2013), PBM‐localized STRL transporters putatively for 2‐MAG transport, and chloroplast‐localized TGD homologues responsible for ER‐plastid transport of larger lipid molecules such as PAs (Kelly et al ., 2016). These discoveries support the notion that lipid transport during nodulation is a significant event, consistent with the results of previous studies (Lei et al ., 2014; Pii et al ., 2009; Emerich and Krishnan, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Among those, fatty acids synthesis(PUSH), FAD2, FAD3 [11], KCSs [12]or MYB1 [13] represent the key for fatty acids composition alteration. FAX1 and FAX2 facilitate fatty acids transport from plastids for improving seed oil accumulation [14,15]. In the Kennedy pathway associated with TAG and membrane lipid synthesis (PULL), acyltransferases such as Lysophosphatidic acid acyltransferase (LPAAT) [16], diglyceride:acyltransferase (DGAT) [17],and Phospholipid diacylglycerol acyltransferase1 (PDAT1) [18] are important for TAG synthesis.…”
Section: Introductionmentioning
confidence: 99%